Legal Mismatch on Illegal Sand Mining in Indonesia: an Example in Sleman, Indonesia - Paramitha Susanti Putri; Trisno Raharjo (Rechtsidee, 2018)
The purpose of this study was to determine the implementation of regulations on illegal sand mining activities in Sleman Regency. The approach used is a legal regulation approach. The results of the study found that the implementation of regulations in illegal sand mining activities in Sleman Regency had not been implemented properly. In fact there are many violations committed by miners in running their businesses, and many mining activities are carried out illegally without having a mining business permit. In addition, the obstacle faced in implementing the regulation is that the miners believe that the sand they take is a blessing due to the eruption of Mount Merapi, so they assume that they can mine in large quantities. In addition, there are limitations to regional budgets that often become obstacles in implementing reclamation as an act of restoring environmental damage carried out by the Environment Agency both at the provincial and district / city levels as well as the limited number of personnel and experts.